Thriving in Uncertainty: How Entrepreneurial Orientation, Online Marketing, and Product Innovation Drive Rural MSME Performance in VUCA Times - Santosa, Allicia Deana; Sugiarti, Rubi’ah; Rahayuningrat, Prahita Sri; Kurniawan; Ardiani, Gusti Tia (Jurnal Bisnis dan Manajemen, 2025)
In an era increasingly characterized by volatility, uncertainty, complexity, and ambiguity (VUCA)—driven by factors such as geopolitical conflicts, economic instability, and global disruptions—Micro, Small, and Medium Enterprises (MSMEs) must adopt adaptive strategies to ensure survival and growth. This study investigates the role of Entrepreneurial Orientation (EO) in enhancing MSME performance under VUCA conditions, with a focus on the mediating roles of Marketing Capabilities, Social Media Marketing, and Product Innovation. Drawing from empirical data, the study confirms that EO significantly influences MSME performance both directly and indirectly. The survey was conducted on MSMEs in East Priangan, West Java, using the purposive sampling method, and the data was analyzed using structural equation modeling. EO is shown to enhance product innovation and marketing capabilities, which in turn positively affect the adoption of social media marketing and overall business performance. Additionally, both product innovation and social media marketing are found to contribute independently to performance outcomes. These findings contribute to entrepreneurship and strategic management literature by presenting an integrated model that explains how MSMEs can leverage entrepreneurial behavior and digital strategies to navigate uncertainty. Practically, the study highlights the importance of developing marketing and innovation capabilities as a pathway to MSME resilience and competitiveness in today’s complex environment.